2011
DOI: 10.1007/s00436-011-2315-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic characterization of the chimeric surface antigen 1 and 2 (SAG1/2) of Toxoplasma gondii expressed in the yeast Pichia pastoris

Abstract: In this study, we successfully expressed a chimerical surface antigen 1 and 2 (SAG1/2) of Toxoplasma gondii in Pichia pastoris. Eighty human serum samples, including 60 from confirmed cases of toxoplasmosis, were tested against the purified recombinant SAG1/2 in Western blots. Results of Western blots targeted at Toxoplasma IgG and IgM showed that the recombinant SAG1/2 reacted with all sera from the toxoplasmosis cases but none with the Toxoplasma-negative serum samples. These results showed that the P. pasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…In addition, these proteins do not contain contaminants derived from the bacterial cells and, therefore, do not give cross-reactions with human sera. In recent years, the Pichia expression system in particular has been used successfully to produced numerous T. gondii recombinant antigens (22,24,75,(80)(81)(82)(83). Thus, there is a need to obtain the new recombinant antigens in different eukaryotic expression systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these proteins do not contain contaminants derived from the bacterial cells and, therefore, do not give cross-reactions with human sera. In recent years, the Pichia expression system in particular has been used successfully to produced numerous T. gondii recombinant antigens (22,24,75,(80)(81)(82)(83). Thus, there is a need to obtain the new recombinant antigens in different eukaryotic expression systems.…”
Section: Resultsmentioning
confidence: 99%
“…Their research demonstrated that the IgM Rec-ELISA found 70% of serum samples from infants with congenital toxoplasmosis to be positive, whereas the commercially available assays used (ELFA-IgM [bioMérieux, France] or ETI-TOXOK-M [DiaSorin, Italy]) found positive results for only 35% of the infected infants (46). Furthermore, different chimeric proteins have also been shown to be very effective in detecting specific anti-T. gondii antibodies in human serum samples (Table 3) (75)(76)(77)(78)(79). In 2012, Holec-Gąsior et al (76) showed that the sensitivity of the IgG ELISA for the MIC1-MAG1 chimeric protein was almost as high as that for the Toxoplasma lysate antigen (TLA), 90.9% and 91.8%, respectively, whereas the sensitivities of IgG ELISAs for the mixture of two recombinant proteins (rMAG1 and rMIC1ex2) or for single recombinant antigens were definitely lower, 69.1% for the mixture, 75.5% for rMIC1ex2, and 60% for rMAG1.…”
Section: Chimeric Antigens and Multiepitope Peptidesmentioning
confidence: 99%
“…Previous studies have reported the potential of various specific antigens of T. gondii such as the surface proteins [13, 14], microneme proteins [15], rhoptry proteins [16, 17], and dense granule proteins [18, 19] as seromarkers, either as single or multiantigen for detection of T. gondii -specific serum antibodies against acute (recently acquired) or/and chronic (distant past) Toxoplasma infection.…”
Section: Introductionmentioning
confidence: 99%
“…The identification and characterization of Leishmania histone antigenic protein fractions, specifically those involved in immune response, and the production of the corresponding recombinant proteins in yeast expression systems such as Pichia pastoris could provide interesting perspectives (21). In fact, this expression system allows eukaryotic protein folding and posttranslational modifications of target proteins, which may offer more specific and sensitive tools for VL diagnosis.…”
Section: Discussionmentioning
confidence: 99%